Comparison of the diagnostic utility of 99mTc-PSMA scintigraphy versus 68Ga-PSMA-11 PET/CT in the detection of metastatic prostate cancer and dosimetry analysis: a gamma-camera-based alternate prostate-specific membrane antigen imaging modality. Issue 5 (30th December 2020) - Singh, Baljinder; Sharma, Sarika; Bansal, Parul; Hooda, Monika; Singh, Harmandeep; Parihar, Ashwin Singh; Kumar, Ajay; Watts, Ankit; Mohan, Ravi; Singh, Shrawan K.
Abstract : Objective: The present study was performed for head-to-head comparison between 68Ga-prostate-specific membrane antigen (PSMA) PET/computed tomography (CT) and 99mTc-PSMA whole-body and regional single-photon emission computed tomography (SPECT)/CT for the detection of prostate cancer metastases. Methods: Ten patients with metastatic prostate cancer underwent 99mTc-PSMA whole-body scan after intravenous injection of 230–330 MBq 99mTc-PSMA. Anterior and posterior whole-body images were acquired at 10 min, 2, 4 and/or 5/6 h post-injection. Additional SPECT/CT images were acquired for the involved sites, where planar images did not clearly identify the metastatic sites. All patients also underwent whole-body 68Ga-PSMA PET/CT and the results between the two techniques were compared for the detection of the metastatic lesions. Dosimetry analysis of the 99mTc-PSMA studies was performed using the MIRD-OLINDA approach. Results: 68Ga-PSMA PET/CT detected lesions in all 10 patients, whereas 99mTc-PSMA imaging detected lesions in 9/10 patients. 68Ga-PSMA PET/CT imaging identified a total of 112 PSMA avid metastatic lesions compared to 57 (51%) lesions on 99mTc-PSMA imaging. Eighteen out of 57 lesions were detected only on delayed 99mTc-PSMA imaging at 4 h and/or 6 h. The regional 99mTc-PSMA SPECT detected 51/83 (61.0%) lesions seen on 68Ga-PSMA PET/CT. The dosimetry results demonstrated that 99mTc-PSMA provided organs' radiation absorbed/effective doses comparable with 99mTc-PSMA imaging. Conclusion: Whole-body 99mTc-PSMA combined with regional SPECT/CT could be a potential alternative to 68Ga-PSMA PET for the detection of the advanced stage metastatic prostate cancer and for response evaluation to PSMA-based targeted therapies.